ta có \(\frac{a}{b}=\frac{c}{d}\)
=>\(\frac{a}{c}=\frac{b}{d}\)(1)
Từ (1) => \(\frac{a^{1005}}{c^{1005}}=\frac{b^{1005}}{d^{1005}}=\frac{a^{1005}+b^{1005}}{c^{1005}+d^{1005}}\)(2)
Từ (1) => \(\frac{a}{c}=\frac{b}{d}=\frac{a+b}{c+d}\)
=>\(\left(\frac{a}{c}\right)^{1005}=\left(\frac{b}{d}\right)^{1005}=\left(\frac{a+b}{c+d}\right)^{1005}=\frac{\left(a+b\right)^{1005}}{\left(c+d\right)^{1005}}\)(3)
mà \(\left(\frac{a}{c}\right)^{1005}=\frac{a^{1005}}{c^{1005}}\)
từ 2 zà 3 => ghi lại cái cần chứng minh nha ( dpcm)